Woven kenaf bast fibre as an alternative for glass fibre stockinette in laminated composite structure to fabricate prosthetic leg socket - Che Me, Rosalam (2012)
Artificial limbs may be needed for a variety of reasons including disease, accidents, and congenital defects. As people’s bodies change over time, due to growth or change in body weight, the artificial limbs have to be changed periodically or adjusted by time. This constant need to change becomes costly if the material used is expensive. This study emphasized on the sockets part as of prosthetic leg as they are require replacement due to wear and tear, as well as to maintain the comfort of wearers. Presently, socket of prosthetic leg is made of Glass Fibre Reinforced Plastic (GRFP). In this study, woven kenaf fibre is used in one or two layers of the laminated composite as a replacement for glass fibres. The study hypothesized that woven kenaf fibre mat can be reinforced in the existing laminated composite structure to replace or as an alternative for glass fibre stockinette to fabricate socket of prosthetic leg. Basically, the current research aimed to prepare the laminated woven kenaf composites to compare with the existing lamination structure (or control) in terms of their mechanical (tensile, flexural and impact) and physical (density and moisture content) properties in identifying both strengths and weaknesses. A true experiment designwas adopted to quantify, if there is any significant difference between four variables which consist of the control and three proposed kenaf laminated composites. These composites were prepared using sandwich layering or lamination technique, adopting a similar technique used to fabricate sockets of prosthetic legs. Results of the study suggest that the incorporation of kenaf in the existing composite structure has resulted in the positive improvement in the mechanical and physical properties. The incorporation of one layer of woven kenaf bast fibre (composite 2) has proven that this particular composite is best in tensile and tensile Young’s Modulus and in flexural strength. Whereas, inclusion of two layers of woven kenaf bast fibre (composite 3) has resulted in giving the highest value of Izod impact strength, flexural Young’s modulus and density. Further analysis discovered that there is no significant difference between these two composites. Therefore, this finding suggests that the best proposed material (laminated woven kenaf fibre composite) to be used as an alternative material for the existing (glass fibre) laminated composite to make socket of prosthetic leg is composite 3 which contains two layers of woven kenaf bast fibre. Although this composite does not contain glass fibre, it has compatible qualities to fabricate socket which resulting in providing alternative material which is more cost efficient and considered as ‘Green’. A prototype of prosthetic leg integrated with socket which is made of the best proposed laminated composites (composite 3) was made to verify the success of this finding throughout this study.Additionally, this prototype also proved that woven kenaf laminated composite is able to be produced commercially to save the total cost of manufacturing the prosthetic leg since kenaf fibre is cheaper as compared to glass fibre.